INFLUENCE OF SOCIAL MEDIA MARKETING ON BUYING BEHAVIOR OF MILLENNIAL TOWARDS SMART PHONES IN BANGALORE CITY - JagadeeshBabu MK, Dr. SaurabhSrivastava, Smita ManoharGaikwad, Dr. AditiPriya Singh, Mahabub Bahsa S (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose: The number of Indian Social Media users is increasing day by day and a lot of Business firms are moving towards social media marketing to enhance their branding and marketing strategies. This study aims at examining the Usage of social media platforms and its impact on the buying behavior of the consumers. Design/methodology/approach: Certainly this analysis is Exploratory in nature. Primary data is obtained from consumers of social media in their Millennials. 165 respondents are estimated on the basis of the Cochran Method of uncertain population sample size. The questionnaire is divided into four sections including Rating scale and Likert scale questions and the questionnaire's convergent-divergent validity is also tested. The data analysis is performed by explaining the rankings and then using SPSS Version 25 and AMOS R Version 23 Tools to test the hypothesis. The study's focus is geographically restricted to City of Bangalore and Millenials. Findings: Study findings revealed that Facebook is the most preferred platform for social media, and that Youtube is the most reliable. On social media marketing the Millenials expressed strong positive perceptions. The majority of the respondents said that the social media marketing influences their buying behaviour. Regardless of the demographic features, social media usage among millenials remains the same. Originality/value: This paper is the first attempt to study the influence of social media marketing on the Millenials in Purchase of smart phones.